# PLEASE solve the quadratic equation by factoring. (x + 1)(x − 3) = 5?

Relevance
• MyRank
Lv 6
4 years ago

(x+1) (x-3) = 5

Multiplied by (x+1) × (x-3)

(x² – 3x + x – 3)

(x² – 2x – 3) = 5

x² – 2x – 3 – 5 = 0

x² – 2x – 8 = 0

ax² + bx + c = 0

x² – 2x – 8 =0

x² – 4x + 2x – 8 = 0

x(x – 4) + 2(x – 4) = 0

(x – 4) (x + 2) = 0

(x – 4) = 0

x = 4

x + 2 = 0

x = - 2

Verified :

x² – 2x – 8 = 0

put x = 4

(4)² – 2(4) – 8 = 0

16 – 16 = 0

0 = 0

x² – 2x – 8 = 0

put x = -2

(-2)² – 2(-2) – 8 = 0

4 + 4 – 8 = 0

0 = 0.

• 4 years ago

x=4 x=-2

• 4 years ago

Apply FOIL

x^2 - 3x + x - 3 = 5

x^2 - 2x - 8 = 0

(x - 4)(x + 2) = 0

x -4 = 0

x = 4

&

x + 2 = 0

x = -2

• Anonymous
4 years ago

expand as x² - 2x - 3 = 5

put into standard equation form: x² - 2x - 8 = 0

factor: (x - 4)(x + 2) = 0

can you take it from here so you can tell your instructor that you “completed” the exercise? if not, gl!

i would give you the final answer to your question, but then you would have to split the credit with me...

i am sure one of my y!a colleagues shall supply you with the specific answer to this exercise... but that shall not help you next time, and there shall be a next time!

• Colin
Lv 7
4 years ago

(x + 1)(x − 3) = 5

Multiply out...

x^2 - 3 - 2*x = 5

Collect like terms...

x^2 - 2*x - 8 = 0

Factorise...

(x - 4)*(x + 2) = 0

Solve...

x = 4 or x = -2

Lv 7
4 years ago

(x+1)(x-3) = 5

x²-2x-3 = 5

x²-2x-8 = 0

(x-4)(x+2) = 0

x = 4,-2

• Anonymous
4 years ago

(x+1)(x-3) = 5

x^2-2x-3=5

x^2-2x-8=0

(x-4)(x+2) = 0

x=4 or x=-2